Sorry about the typo in the previous response.

`v*t = s - (1/2)*a*t^2`

=> `v = s/t - (1/2)*a*t`

**In terms of other variables **`v = s/t - (1/2)*a*t`

The expression for v has to be determined in terms of the other variables given that `s = vt + 1/2at^2`

s = `vt + 1/2at^2`

=> `v*t = s - (1/2)*a*t^2`

=> `v = s/t + (1/2)*a*t`

**In terms of the other variables **`v = s/t + (1/2)*a*t`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now